Changes in Phosphorus Fractions on an Acidic Soil Induced by Phosphorus Fertilizer, Organic Matter and Lime - Hartono, A; Vlek, P.L.G.; Moawad, A; Rachim, A (Jurnal Ilmu Tanah dan Lingkungan, 2001)
One month of incubation experiment was implemented to evaluate the changes of phosphorus fraction in inorganic P (Pi) and organic P (Po) induced by phosphorus fertilizer (KH2P04), cow manure ( manure) and CaC03 (lime). A 0.5 kg oven-dried weight of arable layers of Latosol from Darmaga, Bogor was used in this study. The rates of manure were 0, 12.5 and 25 ffha, lime were 0, 1, 3 times the CaC03 equivalent required to neutralize exchangeable aluminum amounting to 0, 3.01, 9.03 t/ha respectively and the rates of phosphorus fertilizer in KH2P04 were 0, 40 and 80 kg Plha. All treatments increased resin-Pi (biologically available P). Application of phosphorus fertilizer also increased NaHC03-Pi which is also included as biologically available PI whi!e manure and lime only tended to increase this fraction. Phosphorus fertilizer and manure application were able to enhance NaOH-Pi (moderately resistant P related to AI-P and Fe-P ) but lime did not affect it. Phosphorus fertilizer, manure and lime increased HCI-Pi (moderately resistant P related to Ca-P). The changes of NaHC03-Pi to resin-Pi and P immobilization by microorganism, which was indicated by the increase of NaHCOrPo (readily mineralizable), can be attributed to the decrease of NaHC03- Pi. The increase of NaOH-Pi by phosphorus fertilizer and manure indicated that the complexation of P fixation sites by PO6 and organic acids likely had occurred.